Pengaruh Rasio Profitabilitas dan Rasio Solvabilitas terhadap Return Saham pada Sektor Pertambangan yang Terdaftar di Bursa Efek Indonesia (BEI) Tahun 2019-2023 - Reza, Muhammad; Firayanti, Yuni; Saputra, Edy Suchmawan (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2024)
This research was conducted to test and analyze the effect of the Profitability ratio represented by ROE and ROA while the Solvency ratio represented by DER and DAR on Stock Returns. This research uses secondary data derived from financial and annual reports of companies listed on the Indonesia Stock Exchange (IDX). The population in this research is metal and mineral mining sector companies listed on the Indonesia Stock Exchange (IDX), which publish financial and annual reports during the 2019-2023 period. The number of companies used for the sample in this research is 10 companies and the period is 5 years. The study used a purposive sampling data collection method by conducting a selection stage with certain criteria, so that the total sample in this study was 50 samples. This research is quantitative research while collecting literature study data through various sources, namely books, journals, and the internet. For hypothesis testing in research is multiple linear regression analysis, classical assumption test, and hypothesis testing with the help of SPSS version 29 software with a significance level of 5%. The results of this study indicate that the Profitability ratio represented by Return on Equity and Return on Asset has no effect on Stock Returns, while the Solvency ratio represented by Debt to Equity Ratios and Debt to Asset Ratios has no effect on Stock Returns.